Design and Development of Lifelong Skills-Enhancement e-Programmes Using Monitoring/Evaluation Tools: Exemplars with Policy Recommendations - Ng, Khar Thoe; Muthiah, Jeyaletchumi; Assanarkutty, Shah Assanarkutty Jahan; Sinniah, Deva Nanthini; Cyril, Nelson; Jayaram, Nanthini; Durairaj, Kamalambal; Sinniah, Sivaranjini (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
Developing ‘Future Ready’ learners in preparation of Industrial Revolution (IR) through implementation of lifelong skills-enhancement programmes collaborating with various sectors is the recent global governmental aspiration. In response to call for quality technology-enhanced ‘Science, Technology, Reading, Engineering, Arts, Mathematics’ (STREAM) education, SEAMEO RECSAM initiated the ‘Learning Science and Mathematics Together’ [LeSMaT (Borderless)] project-based programme under the Golden SEAMEO Basic Education and Student Networking involving blended-mode lifelong education. This article reports SEAMEO Inter-Centre Collaboration (ICC) Education 4.0 project initiative as an offshoot programme of LeSMaT involving Design and Development Research (DDR) in developing lifelong skills-enhancement e-programmes integrating STREAM education with evidence-based output under sub-themes identified from LeSMaT(Borderless) involving ‘Analysis, Design, Development, Implementation, Evaluation’ (ADDIE) instructional model. ‘Analysis’ of these sub-themes were made to develop criteria as guiding focus for project teams to design technology-enhanced learning (TEL) output that could showcase the knowledge/skills required during IR4.0. Literature research was also made on existing e-programmes fulfilling SEAMEO’s priorities. During ‘Design and Development’ phases, e-surveys were developed as monitoring/evaluation tools for tracking of skills-enhancement e-programmes in line with Sustainable Development Goals (SDGs).  During ‘Implementation/Evaluation’ phases, qualitative/quantitative data collection/analysis methods were implemented involving case study and validation of e-survey entitled ‘Motivation towards STREAM education’ (MoToS). The qualitative analysis integrating ‘type 4’ multiple-case design includes analysing output illustrating curriculum innovation through transdisciplinary studies reflecting Education 4.0 and SDGs whereas quantitative method involved Rasch model to validate MoToS  to monitor/evaluate participants’ engagement  in 1st Regional Workshop on SEAMEO-ICC Education 4.0. The findings using Rasch analysis in the ‘Evaluation’ phase revealed that MoToS is reliable with measure of CA 0.98 internal consistency and ‘feeling stressed on STREAM’ is the most difficult item.  After the e-course series 2020-2022, participants' output was examined using ‘Cross-Case Analysis’ (CCA), ‘Within/Exemplary-Case Analysis’ (WCA/ECA). The e-course series produced evidence-based SDG-related outputs with exemplars integrating SEAMEO Priority Areas No.7 and No.5. Policy recommendations and suggestions for future studies related to Education 4.0 are discussed including developing innovative programmes to improve transdisciplinary quality education